A comprehensive evaluation method for plateau freshwater lakes: a case in the Erhai Lake - Zhuqing Wen (Taylor & Francis Group, 2021)
The study first systematically assessed the ecosystem health status of the plateau freshwater lake of Erhai Lake in Yunnan Province of China, using the revised Freshwater Health Indicator methodology, which comprised three components, i.e., “Ecosystem Vitality,” “Ecosystem Services,” and “Governance and Stakeholders.” To better reflect the real health status of the basin, the cask short board effect was considered during aggregation of the indicators. In addition, analysis of the coupling coordination relationship among the three components was conducted to study the mutual influences among them as well as the comprehensive development level of the studied area. Basically, the ecosystem of the Erhai Lake basin remained healthy during the studied period according to the research due to specific measures and actions taken to manage the environmental problems caused by a former local economic development and urbanization process. However, there were still aspects to improve for more sustainable ecosystem management and utilization in the basin. The “short boards” of the Erhai Lake basin show room for improvement in local freshwater ecosystem management and underline governance problems that need to be addressed. Suggestions are provided for the local stakeholders consequently for the more sustainable development of the studied basin.